A greenhouse approach for value cultivation. (3rd July 2016) - Dahlgaard, Jens J.; Pugna, Adrian; Potra, Sabina; Negrea, Romeo; Mocan, Marian
Abstract : The present paper explores design requirements to take into consideration when designing and developing new products or services. The purpose of this article is to develop a strategic approach for analysing variations between potential customer needs in order better to understand what qualities should be further cultivated before product launch. This new approach is called 'A Greenhouse Approach for Value Cultivation' . Case study data of a new web-based customisation service for a Romanian shoe manufacturing company has been re-analysed by using questionnaire data on 166 respondents' perceptions on 14 attributes' importance and value. A nonlinear regression model was developed and used to understand relations between importance and value. Such relations were used together with the Greenhouse Model to better understand the service attributes' potential life cycles if selected for further cultivation. The Greenhouse Model envisages new perspectives of the evaluation of customer needs to support strategic decision-making regarding further value cultivation for profound affection (= customer delight). Even if there is a need for further tests the suggested 'Greenhouse Approach for Value Cultivation' is regarded as a new and original contribution to the theory of attractive quality creation which deepens its position in the theory of attractive quality and transforms it into a practical management tool to support new product and service design.